Significant Correlation Between Cutaneous Abundance of Streptococcus and Psoriasis Severity in Patients with FBXL19 Gene Variants - Malin Assarsson; Jan Söderman; Oliver Seifert (Medical Journals Sweden, 2024)
Psoriasis results from both genetic predisposition and environmental triggers, such as Streptococcal infections. This study aimed to explore the correlation between the abundance of the Streptococcus genus on the skin and psoriasis severity in individuals carrying specific psoriasis-associated genetic variants. Studying 39 chronic plaque psoriasis patients, the elbow skin microbiome and 49 psoriasis-related single nucleotide polymorphisms (SNPs) were analysed using a MiSeq instrument for 16S rDNA sequencing, and CLC Genomic Workbench for processing and analysis. Through multivariate linear regression analysis, a positive correlation was found between Streptococcus genus abundance and psoriasis severity in patients with certain FBXL19 gene-related heterozygous SNPs (rs12924903, rs10782001, rs12445568). Conversely, a negative association was observed in patients with homozygous genotypes. Moreover, we identified an association between Streptococcus abundance and psoriasis severity in patients with genetic variants related to IL-22, ERAP1, NOS2, and ILF3. This is the first study highlighting a positive association between Streptococcus skin colonization and psoriasis severity in patients with heterozygous genotypes within the FBXL19 gene region. FXBL19 targets the IL-33/IL1RL1 axis, crucial in infectious diseases and innate immunity promotion. These novel results suggests an intricate interaction among host genetics, Streptococcus skin colonization, and psoriasis inflammation, offering potential avenues for novel treatment approaches.